Few Excited State Energies and Chemical Potential Energy of 87Rb Condensate by Many-Body Approach - Debnath, P. K. (Journal of Scientific Research, 2022)
We consider experimental 87Rb condensate which is trapped by harmonic plus quartic trap [V(r) = ½mω2r2 + λr4]. Keeping similarity with experiments, the anharmonic parameter (λ) is considered as a controllable parameter. The excited state energies of stable Bose-Einstein condensate are strongly influenced by the presence of an anharmonic term, even when the interatomic interaction is repulsive. The necessary dependencies of excited state energies of the trapped condensate on λ are discussed in detail. In addition, the variation of chemical potential energy as a function of λ is also investigated to explore the role of interaction. The many-particle Schrödinger equation is solved by the potential harmonic expansion method, where all possible two-body correlations are considered by utilizing the correlated two-body basis function. Specifically, we present a clear physical explanation of excited state energies and chemical potential energy of the experimental repulsive condensate confined by the anharmonic trap.